Ambition Of Minke Reflected At Pramoedya Ananta Toer's Novel This Earth Of Mankind (1975): A Psychoanalytic Approach - Hernasari, Putri Sulistyo; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2014)
This research aims at knowing of ambition Minke and what individuality character based on reflected in real story of novel This Earth of mankind is suitable with the theory by Sigmund Freud. The type of this research is descriptive qualitative. Type of the data and the data source taken from two data source: primary and secondary. The primary data source is This earth of Mankind novel written by Pramoedya Ananta Toer's released in 1975. And the secondary data sources are taken from books theory, other source and internet related to the study. The technique of collecting data is documentation. The steps are reading novel, classfying and analyzing the data, taking note and browsing to the internet. Based on the analysis, the researcher portrays some conclusions, the study shows that the problem faced by the major character is the own psychology condition to decide the appropriate ways for his life. This novel is about ambition of Minke to love for Annelies.